Analisis Overall Equipment Effectiveness (OEE) pada Mesin Pencacah Tongkol Jagung di PT Multindo Anugerah Perkasa - Muthia Aulia Rahima; Abdul Mail; Ahmad Padhil (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
PT Multindo Anugerah Perkasa is a third party company that supplies fuel in the form of corncob biomass to PT PLN Nusantara Power. Overall Equipment Effectiveness (OEE) is a method used to measure the effectiveness of machines or equipment. To get OEE, 3 ratio calculations are required, namely Avaliability, Performance Rate, and Quality Ratio. The World Class OEE standard from JIPM is 85%. This research was carried out on a corn cob chopping machine at PT Multindo Anugerah Perkasa because there was no calculation of the effectiveness of the machine, the machine used to chop corn cobs often underwent maintenance outside of the scheduled maintenance schedule. The results of the OEE calculation for this corncob chopping machine show that the effectiveness of the machine still meets world class effectiveness standards, namely 85% with an Avaliability value of 92% above JIPM standards, a Performance Rate of 93% and a Quality Ratio value of 100% in this case quality The results produced perfectly meet JIPM standards, so this corn cob chopper machine is still effectively used to fulfill the biomass supply to PT PLN Nusantara Power.